Potential of Pseudomonad Fluoresen as Control of Plant Diseases - Silviana Okwisan; Linda Advinda; Dezi Handayani; Dwi Hilda Putri; Irma Leilani Eka Putri (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
The use of fertilizers and pesticides provides various side effects such as environmental pollution and higher production costs due to the high prices of fertilizers and pesticides. Therefore it is necessary to look for other alternatives to control plant diseases. One of the safe and environmentally friendly control measures is to use biological control agents. Fluorescent pseudomonads are antagonistic bacteria that are widely used as biological agents for fungi, pathogenic bacteria and viruses. Biological control using fluorescent pseudomonads has been studied for its effectiveness in suppressing plant diseases. This study aims to collect and analyze articles related to the potential of fluorescent pseudomonads in controlling plant diseases. This type of research is research that uses the literature review method and collects literature using internet sources from the Google Scholar database. The stages consist of identification, screening, eligibility and acceptance. Based on the articles collected, it was found that fluorescent pseudomonads are potential and effective in controlling various plant diseases.